Analisis Ekuitas Merek Aqua Berdasarkan Persepsi Kualitas Merek (Brand Perceived Quality) Pada Pengguna Media Sosial Instagram - Purwaningrum, Chanissa; Adhelya Putri, Tiara; Saulina, Tania (Rifa'Institute, 2021)
PT AQUA Golden Mississippi, Tbk is one of the many brands thatproduce mineral water with various packaging needed. AQUA asthe market leader in the bottled water product category, has a strongbrand equity. In addition, AQUA increases the perceived quality inthe eyes of consumers by adding a variety of choices of bottleddrinking water of various sizes. In general, the purpose of this studyis to get an overview of AQUA's brand equity, while in more detailthe purpose of this study is to analyze the perception of brand qualityin drinking water in the AQUA brand packaging among the socialmedia users of Instagram. This research is a type of survey research,where the research aims to find out about the measurement of brandequity based on brand perceived quality elements in AQUA brandbeverage products. The number of samples in this study were 374samples, namely 365 women and 9 men. Based on the results of thestudy, it can be concluded from the percentage of 97.9% who chosestrongly agree and agree, that respondents believe in the qualitygiven that AQUA has clear water in the eyes of consumers, 93.3%who voted strongly agree and agree, that the bottled water producedby the AQUA brand does not have a smell or smell in the eyes ofconsumers, 68.2% of AQUA consumers choose strongly agree andagree it is proven that the quality of AQUA is very good, 90.7% whochoose strongly agree and agree, that AQUA is believed to be ahygienic product in the eyes of consumers, 96% who voted stronglyagree and agree, that AQUA can make it easier to consume drinkingwater in the eyes of consumers, 96.3% who choose strongly agreeand agree, that AQUA has an easy logo recognized and rememberedin the eyes of consumers, 96.3% who voted strongly agree and agree,that AQUA has good packaging in the eyes of consumers, 79% whochose strongly agree and agree, that AQUA has the same qualityfrom time to time in the eyes of consumers, 89, 3% who votedstrongly agree and agree that AQUA has a price that is in accordancewith the volume/size in the eyes of consumers